Does the Reform of the Parliamentary and Presidential Threshold Strengthen the Presidential System in Indonesia? - Mahesa Rannie; Retno Saraswati; Fifiana Wisnaeni (Faculty of Law, Sriwijaya University, Indonesia, 2024)
The attempt to purify Indonesia's multiparty presidential system was only reflected after the Third Amendment to the 1945 Constitution. However, it took work to implement it. In practice. Various measures have been taken, including party alliances and introducing voting barriers in parliamentary elections. Therefore, analysing the relationship between electoral thresholds and their ideal proportions in the form of legal-political reforms to strengthen the Indonesian presidential system is interesting. This is in line with the purpose of this study, which is to uncover and analyse the legal politics of electoral thresholds in an attempt to strengthen the presidential system of government in Indonesia. The approach adopted in this study is a theoretical approach with legal, conceptual, comparative and historical approaches. This study concludes that the legitimate political renewal of the electoral vote threshold is not closely related to efforts to strengthen Indonesia's system of multiparty presidential government. The ideal way to reform the legal, political threshold for electoral votes would be to set the parliamentary threshold at 2.5%, but at the same time tighten controls over the parties participating in the election, and the 2.5% threshold serves as President to maintain a balance between the parliamentary and presidential thresholds. In addition, it is also important to strengthen consensus (consensus democracy) among coalition political parties. There is still a desire to abolish the presidential threshold through the People's Representative Council (DPR) instead of the Constitutional Court (MK).